2020
DOI: 10.1177/0886260520976222
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Intimate Partner Violence Among Married Women During COVID-19 Pandemic Restrictions: A Community-Based Study

Abstract: Ethiopia has taken unprecedented preventive measures, such as confinement to home and closure of schools and offices to halt the spread of Corona virus pandemic in the country. Unfortunately, such orders may have been associated with intimate partner violence (IPV) against women but there is no study conducted to assess the magnitude of IPV during the lock-downs in the country. Thus, this study intended to investigate the prevalence and associated factors of IPV against women during the COVID-19 pandemic restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
2
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(97 citation statements)
references
References 33 publications
1
86
2
8
Order By: Relevance
“…Intimate partner violence is currently regarded as the shadow pandemic as the incidence rates have increased during COVID-19 pandemic [ 18 , 29 , 30 ]. Since the outbreak of COVID-19, emerging reports from those on the front line have shown that violence against women, particularly domestic violence, has intensified.…”
Section: Intimate Partner Violence During Covid-19 Pandemic “The Shadow Pandemic”mentioning
confidence: 99%
“…Intimate partner violence is currently regarded as the shadow pandemic as the incidence rates have increased during COVID-19 pandemic [ 18 , 29 , 30 ]. Since the outbreak of COVID-19, emerging reports from those on the front line have shown that violence against women, particularly domestic violence, has intensified.…”
Section: Intimate Partner Violence During Covid-19 Pandemic “The Shadow Pandemic”mentioning
confidence: 99%
“…Few studies point at potential protective factors such as evidence from India [ 146 ] and Ethiopia [ 150 ], which suggests that higher education (for both the victim and the perpetrator) decreases the risk of violence. Levels of intimate partner violence (IPV) were twice as high for illiterate women in Ethiopia as for women who had completed high school.…”
Section: Violence Incidence During the Covid-19 Pandemicmentioning
confidence: 99%
“…The six articles used in this scoping review were each from Iran [20], Ethiopia [21], Italy [22], Brazil [23], Australia [24], and Canada [25]. In addition, four articles focused on cases of domestic violence during the COVID-19 pandemic [21], [22], [24], [25], one article focused on cases of domestic violence in pregnant women during the COVID-19 pandemic [20], and one article focused on tackling domestic violence cases during the COVID-19 pandemic [23].…”
Section: The Characteristics Of Selected Articlesmentioning
confidence: 99%
“…We identified several risk factors related to domestic violence during the COVID-19 pandemic, among others: Illiterate women have an illiterate husband; married to drug users (alcohol, chat, or smoking); and living in a society that is tolerant of violence, financial stress, rarely having contact with family, and friends outside the home during the pandemic [21], [24].…”
Section: Risk Factors For Domestic Violencementioning
confidence: 99%